Nicotinamide riboside alleviates cisplatin-induced peripheral neuropathy via SIRT2 activation. Issue 1 (27th June 2022) - Acklin, Scarlett; Sadhukhan, Ratan; Du, Wuying; Patra, Mousumi; Cholia, Ravi; Xia, Fen
Abstract: Background: Chemotherapy-induced peripheral neuropathy represents a major impairment to the quality of life of cancer patients and is one of the most common dose-limiting adverse effects of cancer treatment. Despite its prevalence, no effective treatment or prevention strategy exists. We have previously provided genetic evidence that the NAD + -dependent deacetylase, SIRT2, protects against cisplatin-induced peripheral neuronal cell death and neuropathy by enhancing nucleotide excision repair. In this study, we aimed to examine whether pharmacologic activation of SIRT2 would provide effective prevention and treatment of cisplatin-induced peripheral neuropathy (CIPN) without compromising tumor cell cytotoxic response to cisplatin. Methods: Using von Frey and dynamic hot plate tests, we studied the use of nicotinamide riboside (NR) to prevent and treat CIPN in mouse model. We also performed cell survival assays to investigate the effect of NAD + supplementation on cisplatin toxicity in neuronal and cancer cells. Lewis lung carcinoma model was utilized to examine the effect of NR treatment on in vivo cisplatin tumor control. Results: We show that NR, an NAD + precursor and pharmacologic activator of SIRT2, effectively prevents and alleviates CIPN in mice. We present in vitro and in vivo genetic evidence to illustrate the specific dependence on SIRT2 of NR-mediated CIPN mitigation. Importantly, we demonstrate that NAD + mediates SIRT2-dependent neuroprotection without inhibiting cisplatin cytotoxic activity against cancer cells. NAD + may, in fact, further sensitize certain cancer cell types to cisplatin. Conclusions: Together, our results identify SIRT2-targeted activity of NR as a potential therapy to alleviate CIPN, the debilitating and potentially permanent toxicity.